Influence of a Latrophilin 3 (LPHN3) risk haplotype on event-related potential measures of cognitive response control in attention-deficit hyperactivity disorder (ADHD) - Fallgatter, Andreas J. (2012)
Current research strategies have made great efforts to further elucidate the complex genetic architecture of attention-deficit hyperactivity disorder (ADHD). The present study examined the impact of an LPHN3 haplotype that has recently been associated with ADHD (Arcos-Burgos et al., 2010) on neural activity in a visual Go-NoGo task. Two hundred sixteen adult ADHD patients completed a Continuous Performance Test (CPT) while the ongoing EEG was simultaneously recorded. Results showed that patients carrying two copies of the LPHN3 risk haplotype (n=114) made more omission errors and had a more anterior Go-centroid of the P300 than patients carrying at least one LPHN3 non-risk haplotype (n=102). Accordingly, the NoGo-Anteriorization (NGA; topographical ERP difference of the Go- and NoGo-condition), a neurophysiological marker of prefrontal functioning, was reduced in the LPHN3 high risk group. However, in the NoGo-condition itself no marked differences attributable to the LPHN3 haplotype could be found. Our findings indicate that, within a sample of ADHD patients, the LPHN3 gene impacts behavioral and neurophysiological measures of cognitive response control. The results of our study further strengthen the concept of an LPHN3 risk haplotype for ADHD and support the usefulness of the endophenotype approach in psychiatric and psychological research.